Fostering Employee Ambidexterity: The Role of High-Performance Work System and Ambidextrous Leadership - Amare Werku Ijigu; Abebe Ejigu Alemu; Abdurezak Mohammed Kuhil (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to empirically investigate the moderating effect of ambidextrous leadership in the relationship between high-performance work systems (HPWS) and employee ambidexterity. Design/Methods/Approach: By integrating social exchange theory and the abilities, motivation, and opportunity (AMO model of human resource management), using a sample of 387 non-supervisory sales representative employees of Ethio-Telecom in Addis Ababa, Ethiopia. The proposed hypotheses were examined using structural equation modeling, SPSS plus AMOS software. Findings: The study reveals that HPWS has a positive and significant effect on employee ambidexterity. In addition, ambidextrous leadership moderates the relationship between a high-performance work system and employee ambidexterity. Furthermore, at the high level of ambidextrous leadership, the effect of a high-performance work system on employee ambidexterity is stronger. Originality: This study adds ambidextrous leadership as a moderator in the relationship between HPWS and employee ambidexterity, creating a new theoretical framework. Similarly, in stressing an evident gap in the relationship between HPWS and employee ambidexterity, this paper attempts to explain further how ambidextrous leadership moderates the effect of HPWS on employee ambidexterity. Practical/Policy implication: The study result reveals that the supervisors' high ambidextrous leadership behaviors and well-crafted HPWS enhance the sales representative's desire to engage in exploitative and exploration activities. In light of this, it makes sense that ambidextrous leadership is necessary to greatly affect HPWS and employee ambidexterity, enabling the organization to guide its leadership selection and development.